Engineering - Yurt, Nasuhi (New Jersey : Everest Production, 2008)
Explores the world of engineering, the application of scientific, economic, social, and practical knowledge, in order to design, build, and maintain structures, machines, devices, systems, materials and processes.
Executive producer, Adem Kalac.
Host : Laura Wells.
DVD format.
Keywords: Engineering